2021
DOI: 10.3390/app11083510
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Understanding the Anticancer Properties in Human Prostate and Breast Cancer Cell Lines of Chemically Characterized Methanol Extract from Berberis hispanica Boiss. & Reut

Abstract: The current research was conducted to investigate the chemical profile, antiproliferative, and antioxidant activities of methanol extracts obtained by two different methods including maceration and Soxhlet from Berberis hispanica Boiss. & Reut. Antiproliferative activities were evaluated by the MTT (3-(4, 5-dimethylthiazolyl-2)-2, 5-diphenyltetrazolium bromide) assay in four human cancer cell lines including prostate (LnCap and 22 RV1) and breast cancer (MDA-MB-231 and MCF7). The antioxidant power was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…This extract showed substantial anticancer efficacy against human breast cancer MCF-7 and MDA-MB-231 ( Isbilen and Volkan, 2021 ). 1,2-benzenedicarboxylic acid was also reported to be present within the methanolic bark extract of Berberis hispanica and also showed anticancer potential against human breast cancer (MCF-7 and MDA-MB-231 cells) and human prostate cancer LnCap and 22 RV1 cells ( El Fakir et al, 2021 ). Similarly, dodecane was also reported from the GC-MS analysis of endophytic fungi Talaromyces purpureogenus extracts and showed its anticancer efficacy against HPV18 + human cervical cancer HeLa cells ( Kumari et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This extract showed substantial anticancer efficacy against human breast cancer MCF-7 and MDA-MB-231 ( Isbilen and Volkan, 2021 ). 1,2-benzenedicarboxylic acid was also reported to be present within the methanolic bark extract of Berberis hispanica and also showed anticancer potential against human breast cancer (MCF-7 and MDA-MB-231 cells) and human prostate cancer LnCap and 22 RV1 cells ( El Fakir et al, 2021 ). Similarly, dodecane was also reported from the GC-MS analysis of endophytic fungi Talaromyces purpureogenus extracts and showed its anticancer efficacy against HPV18 + human cervical cancer HeLa cells ( Kumari et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“… 17 It has been reported that after an incubation period of 72hrs, methanolic extract of Berberis hispanica showed a 50% reduction in the proliferation of MCF-7 cells. 18 One more study reported the anti-proliferative effect of Zaleya pentandra extract against MCF-7 cells almost 37% after 24hrs of treatment. 19 While another study reported the anti-proliferative effect of Allium autumnale extract which showed 98.5%, 99.68%, and 99.77% reduction in MCF-7 cells growth after 24hrs, 48hrs, and 72hrs of treatment, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…About 60% of medications allowed for cancer treatment are of a natural source. The anticancer activity was not reported and published by other researchers to date, but different species of genus Berberis are reported to have in vitro cytotoxic activity against different destructive cell lines (El Fakir et al, 2021;Ilyas et al, 2021). An evaluation of the anticancer activity of the ethanolic extracts of the bark, leaves, and roots of the B. baluchistanica plant was done by using MTT cell assay against HeLa cell line.…”
Section: Discussionmentioning
confidence: 99%